Girl anonymous - Dodd, Christina (Canary Street Press, 2025)
"As a child, Maarja Daire saw her mother ignite an explosion that killed vengeful mob boss Benoit Arundel--and herself--to save Maarja's life. Maarja's been on the run ever since . . . fleeing from intimacy, from love, from consequences. Now an adult, Maarja hides in plain sight as a fine arts mover, transporting priceless belongings. Work for a new client brings her to the mansion where the fateful blast from her childhood occurred. There she meets Dante, the ruthless, scarred and brooding Arundel family boss. He watches her with dark intent . . . but does he remember her? Will he use her to take revenge for his father's death? A chance turn of events earns her his trust, when she courageously leaps into flames to rescue his mother. And what happens between them in the darkness sets their worlds on fire, as Maarja recklessly abandons her lifelong caution and self-imposed isolation. Dante calls the urgency between them Fate. Maarja denies him, struggles against his domination and fights the slow erosion of her resistance. When he vows to end the ancient feud, his hidden enemies seize the opportunity to destroy him and the woman he will do anything to protect. Bound together by destruction, passion and destiny, Dante and Maarja must navigate uncharted depths of betrayal and loss, to create a new beginning . . . before the flames of the vendetta consume them"--